Age-not Charlson Co-morbidity Index-predicts for mortality after stereotactic ablative radiotherapy for medically inoperable stage I non-small cell lung cancer. (August 2017) - Holmes, Oliver Edwin; MacRae, Robert; Cook, Graham; Cross, Peter; Nair, Vimoj; Marginean, Horia; Pantarotto, Jason R.
Abstract: Purpose: In this single institution retrospective study of patients with stage I medically inoperable non-small cell lung cancer (NSCLC) treated with stereotactic ablative radiotherapy (SABR) we attempt to model overall survival (OS) using initial prognostic variables with specific attention on the Charlson co-morbidity index (CCI). Methods: Between 2008 and 2013, 335 patients with medically inoperable stage I NSCLC were treated with SABR or hypofractionated radiotherapy (50–60 Gy in at least 5 Gy or 4 Gy fractions respectively) at our institution. Medical comorbidities and Charlson scores were determined by individual chart review. Patients were stratified into 3 groups based on the CCI score (0–1, 2–3, 4–9) and again based on the age-adjusted Charlson Comorbidity score (aCCI). Cumulative survival for each stratum was determined using the Kaplan-Meier method. Non-significant and confounding variables were identified and discounted from survival modeling. 3 sex stratified Cox regression models were tested: (1) aCCI with age and comorbidity combined; (2) age and CCI; (3) age alone, comorbidity removed. Results: The median survival was 4.4 years and the median follow up 4.7 years. The median CCI and aCCI scores were 2 and 5 respectively. Patients with aCCI 7–12 had an increased hazard of death on univariate analysis HR 2.45 (1.15–5.22 95%CI, p  = 0.02) and -excluding age as a competing variable- on multivariate analysis HR 2.25 (1.04–4.84 95%CI, p  = 0.04). Patients with CCI 4-9 had an increased hazard of death on univariate analysis HR 1.57(1.30–2.90) but not on multivariate analysis. On formalized testing – with either continuous or categorical variables- all three survival models yielded similar coefficients of effect. Conclusion: We identify male gender, weight loss greater than 10% and age as independent prognostic factors for patients treated with medically inoperable NSCLC treated with SABR or hypofractionated radiotherapy. Based on our survival models, age alone can be used interchangeably with aCCI or CCI plus age with the same prognostic value. Age is more reliably recorded, less prone to error and therefore a more useful metric than Charlson score in this group of patients.